Synchronization of Central and Regional Government Policies in Public Services - Aulia, Ajeng Putri; Tambun, Karnita Yolanda (Indonesian Journal Publisher, 2025)
Public service is the face of successful democratic and inclusive governance. In the context of Indonesia as a decentralized state, the role of local governments in delivering public services has become increasingly significant. However, one of the fundamental challenges that continues to surface is the lack of synchronization between central and local government policies. This misalignment not only leads to overlapping authorities and program inefficiencies but also directly impacts the continuity and quality of services that should ideally benefit citizens. This article aims to critically analyze the dynamics of policy misalignment across governmental levels and propose relevant strategies to foster a more adaptive and responsive policy harmonization. Employing a qualitative-descriptive approach based on literature review, the article examines regulations, policy documents, and relevant academic literature. The analysis reveals that the root causes of policy synchronization issues lie in several key factors: weak vertical and horizontal coordination, sectoral ego among institutions, limited institutional capacity at the local level, and the absence of an institutionalized consultative mechanism. To address these challenges, reforms in governance coordination are necessary strengthening the facilitative role of the Ministry of Home Affairs, integrating development planning through a national digital system, and designing a decentralized model that allows contextual flexibility while maintaining the principle of national policy unity. Strong policy synchronization is a vital prerequisite for building public services that are citizen-oriented and aligned with the vision of sustainable national development.